2007
DOI: 10.1097/01.htr.0000265096.44683.6b
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Vocational Rehabilitation Services and Outcomes for Hispanic Clients With Traumatic Brain Injury

Abstract: European Americans were 1.27 times more likely to obtain employment than were Hispanics. Hispanics with work disincentives had lower odds of returning to work and had more unmet basic needs (eg, food, shelter, and transportation) that need to be addressed in the rehabilitation process. Job placement and on-the-job support services were found to significantly improve employment outcomes. However, on-the-job support services were more likely to be provided to European Americans than to Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 12 publications
5
35
0
Order By: Relevance
“…Likewise, Sherer et al's [15] study of race and productivity after TBI included employment as part of the definition of productivity and found that black subjects and other racial minorities were at least 2 times more likely to be unproductive compared with white subjects after controlling for confounding factors. An examination of vocational outcomes for Hispanic subjects after TBI using a large archival database revealed that they were 1.27 times less likely to obtain employment and receive on‐the‐job support services, which is the most significant predictor of successful employment outcomes, than their white counterparts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Sherer et al's [15] study of race and productivity after TBI included employment as part of the definition of productivity and found that black subjects and other racial minorities were at least 2 times more likely to be unproductive compared with white subjects after controlling for confounding factors. An examination of vocational outcomes for Hispanic subjects after TBI using a large archival database revealed that they were 1.27 times less likely to obtain employment and receive on‐the‐job support services, which is the most significant predictor of successful employment outcomes, than their white counterparts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although ethnicity was not a predictor of RTW in our multivariate analysis, it is important to understand the value of cultural context. The issue of culture as a factor that influences health behavior is widely recognized [28][29][30]. A longitudinal study conducted in Israel that examined various factors predicting RTW among more than 45,000 Israelis after traumatic injuries including extremities injuries has recently been published [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present analyses, Hispanic ethnicity was not significantly associated with unemployment ( P =.60); however, previous investigations of Hispanic ethnicity and unemployment have demonstrated a positive association with unemployment. Differences in the results of these studies may be due to differing definitions of TBI, 44 selection of differing years of TBIMS-NDB data, the use of the weighted TBIMS-NDB population, 45 or differing postinjury year of assessment. 14 …”
Section: Discussionmentioning
confidence: 99%